2017
DOI: 10.1039/c7nr06821b
|View full text |Cite
|
Sign up to set email alerts
|

Mucopenetrating micelles with a PEG corona

Abstract: Crossing the intestinal mucus layer is a long-standing challenge for orally delivered nanoparticles carrying therapeutic cargo. We report the assembly of mucopenetrating cargo-loaded micelles using block copolymers consisting of either linear poly(ethylene glycol) (PEG) or bottle-brush poly(oligo(ethylene glycol)methacrylate) (PEG) as the hydrophilic block and poly(caprolactone) (PCL) or poly(cholesteryl methacrylate) (PCMA) as the hydrophobic extension. The micelles were shown to preserve their stability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 56 publications
2
22
0
1
Order By: Relevance
“…The CMC was determined to be 0.17 mg mL −1 for M1 and 0.12 mg mL −1 for M2 (Figure ci and 2cii, respectively). These CMCs were approximately the same as previously measured for poly(cholesteryl methacrylate)‐ block ‐poly(2‐(dimethylamino)ethyl methacrylate) and ∼3× lower than the CMC previously obtained for micelles assembled from of block copolymers with a hydrophobic pCMA block and a pPEGMA extension . However, in the latter case, the method to determine the CMC was different, which might explain this finding.…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…The CMC was determined to be 0.17 mg mL −1 for M1 and 0.12 mg mL −1 for M2 (Figure ci and 2cii, respectively). These CMCs were approximately the same as previously measured for poly(cholesteryl methacrylate)‐ block ‐poly(2‐(dimethylamino)ethyl methacrylate) and ∼3× lower than the CMC previously obtained for micelles assembled from of block copolymers with a hydrophobic pCMA block and a pPEGMA extension . However, in the latter case, the method to determine the CMC was different, which might explain this finding.…”
Section: Methodssupporting
confidence: 82%
“…Since the mucus layer was not perfectly homogenous, determining the amount of green pixels in the different images and independent repeats was tricky, resulting in rather larger error bars. Nonetheless, this cell culture experiments nicely showed the time‐resolved mucopenetrating properties of M1 F , but they were slower in crossing the mucus compared to our previously reported micelles based on pCMA‐block‐pPEGMA that penetrated within 10 min . We would like to note that the integrity of the micelles could not be determined after crossing the mucus.…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…iii) Confocal laser scanning microscopy images of the mucopenetration of Nile‐Red‐loaded micelles (NR‐loaded P6 F micelles) after 10 min incubation using a Caco‐2/HT29‐MTX‐E12 co‐culture. Reproduced with permission 14. 2017, RSC.…”
Section: Mucopenetrationmentioning
confidence: 99%
“…We recently assembled micelles from amphiphilic block copolymers with a PEG corona (Figure 1ai) and demonstrated that these micelles penetrated the mucus in a microfluidic setup (Figure 1aii) and in Caco‐2/HT29‐MTX‐E12 co‐cultures within 10 min (Figure 1aiii). 14 Copolymer of PEG and chitosan complexed with insulin showed PEG‐graft ratio dependent mucus permeation in rat intestine 15…”
Section: Mucopenetrationmentioning
confidence: 99%